The Effect of Firm Size on Financial Performance: The Moderating Role of External Pressure - Oktaviana; Sutarti (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This research aims to examine how company size affects financial performance, with external pressure as a factor influencing this relationship. This research was conducted on companies in the hotel, restaurant, and tourism subsector listed on the Indonesia Stock Exchange (IDX) during the 2024–2025 period. The analysis was conducted using the panel data regression method on 31 companies with a total of 155 data points, to examine how internal company characteristics interact with external pressures, particularly pressure from government regulations. The results indicate that large companies tend to have lower financial performance due to operational inefficiencies and high fixed costs. However, external pressure did not moderate the relationship between firm size and financial performance, meaning government efficiency policies did not directly decrease firm profits. This finding supports the contingency theory that internal factors remain the primary determinants of performance despite external pressures. This research emphasizes that external pressure can be an opportunity for innovation and strategic adaptation. From a practical standpoint, companies in the tourism sector are advised to view efficiency policies as an opportunity to enhance competitiveness and resilience by improving management capabilities